FDA Approval Summary: Pembrolizumab for Recurrent Locally Advanced or Metastatic Gastric or Gastroesophageal Junction Adenocarcinoma Expressing PD‐L1 - Fashoyin‐Aje, Lola; Donoghue, Martha; Chen, Huanyu; He, Kun; Veeraraghavan, Janaki; Goldberg, Kirsten B; Keegan, Patricia; McKee, Amy E; Pazdur, Richard (The oncologist (Dayton, Ohio), 2019)
On September 22, 2017, the U.S. Food and Drug Administration (FDA) granted accelerated approval for pembrolizumab (Keytruda, Merck & Co., Inc., Whitehouse Station, NJ) for the treatment of patients with recurrent, locally advanced or metastatic, gastric or gastroesophageal junction (GEJ) adenocarcinoma with disease progression on or after two or more systemic therapies, including fluoropyrimidine‐ and platinum‐containing chemotherapy and, if appropriate, HER2/neu‐targeted therapy, and whose tumors express programmed death‐ligand 1 (PD‐L1), as determined by an FDA‐approved test. Approval was based on demonstration of durable overall response rate (ORR) in a multicenter, open‐label, multicohort trial (KEYNOTE‐059/Cohort 1) that enrolled 259 patients with locally advanced or metastatic gastric or GEJ adenocarcinoma. Among the 55% (n = 143) of patients whose tumors expressed PD‐L1 based on a combined positive score ≥1 and either were microsatellite stable or had undetermined microsatellite instability or mismatch repair status, the confirmed ORR as determined by blinded independent central review was 13.3% (95% CI, 8.2–20.0); 1.4% had complete responses. Response durations ranged from 2.8+ to 19.4+ months; 11 patients (58%) had response durations of 6 months or longer, and 5 patients (26%) had response durations of 12 months or longer. The most common (≥20%) adverse reactions of pembrolizumab observed in KEYNOTE‐059/Cohort 1 were fatigue, decreased appetite, nausea, and constipation. The most frequent (≥2%) serious adverse drug reactions were pleural effusion, pneumonia, dyspnea, pulmonary embolism, and pneumonitis. Pembrolizumab was approved concurrently with the PD‐L1 immunohistochemistry 22C3 pharmDx test (Dako, Agilent, Santa Clara, CA) for selection of patients with gastric cancer for treatment with pembrolizumab based on PD‐L1 tumor expression. Implications for Practice This report presents key information on the basis for Food and Drug Administration approval of pembrolizumab for the treatment of patients with locally advanced or metastatic gastric or GEJ adenocarcinoma whose tumors express PD‐L1. The report discusses the basis for limiting the indication to patients with PD‐L1‐expressing tumors and the basis for recommending that PD‐L1 status be assessed using a fresh tumor specimen if PD‐L1 expression is not detected in an archival gastric or GEJ cancer specimen. 摘要 2017 年 9 月 22 日,美国食品和药品管理局 (FDA) 对用于治疗患有复发性局部晚期或转移性胃或胃食管连接部 (GEJ) 腺癌且在两次或多次系统治疗(包括含有氟尿嘧啶和含铂化疗以及在适当情况下的 HER2/neu 靶向治疗)之时或之后出现疾病进展以及其肿瘤由经 FDA 批准的试验确定为程序性死亡配体 1 (PD‐L1) 表达的患者的派姆单抗(Keytruda,默克公司,新泽西州,怀特豪斯站)授予快速批准。此项批准以多中心、开放标签、多队列试验(KEYNOTE‐059/队列 1)中持久的总缓解率 (ORR) 实证为依据,该试验招募了 259 名局部晚期或转移性胃或 GEJ 腺瘤患者。在 55% (n =143) 的肿瘤表达 PD‐L1 以综合阳性评分 ≥1 为依据以及肿瘤处于微卫星稳定状态或者未经确定的微卫星不稳定状态或错配修复状态的患者中,经盲性独立中央评审确定的确认 ORR 为 13.3%(95% CI,8.2–20.0);1.4% 的患者出现完全缓解。缓解持续时间的范围介于 2.8+ 个月至 19.4+ 个月之间;11 名患者 (58%) 的缓解持续时间为 6 个月或以上,5 名患者 (26%) 的缓解持续时间为 12 个月或以上。在 KEYNOTE‐059/队列 1 中观察到派姆单抗的最常见 (≥20%) 的不良反应为疲劳、食欲下降、恶心以及便秘。最常见 (≥2%) 的重度药物不良反应为胸腔积液、肺炎、呼吸困难、肺栓塞以及肺炎。派姆单抗已被批准与用于经选胃癌患者的 PD‐L1 免疫组织化学 22C3 pharmDx 试验(Dako,安捷伦,加利福尼亚州,圣克拉拉)一同用于实施基于 PD‐L1 肿瘤表达的派姆单抗治疗。 对临床实践的提示 本报告介绍了美国食品和药品管理局批准将派姆单抗用于治疗局部晚期或转移性胃或 GEJ 腺癌(肿瘤表达 PD‐L1)患者所依据的重要信息。本报告讨论了将适应症限制于 PD‐L1 表达肿瘤患者的依据以及建议在存档的胃或 GEJ 癌样本中未检测到 PD‐L1 表达的情况下使用新鲜的肿瘤样本评估 PD‐L1 状态的依据。 This report presents evidence for FDA approval of pembrolizumab for the treatment of adult and pediatric patients with either unresectable or metastatic, microsatellite instability‐high (MSI‐H) or mismatch repair deficient (dMMR) solid tumors that have progressed following prior treatment, and who have no satisfactory alternative treatment options, or who have metastatic, MSI‐H or dMMR colorectal cancer that has progressed following treatment with a fluoropyrimidine, oxaliplatin, and irinotecan.